2003
DOI: 10.1038/sj.cgt.7700629
|View full text |Cite
|
Sign up to set email alerts
|

Regression of prostate cancer xenografts by a lentiviral vector specifically expressing diphtheria toxin A

Abstract: We have constructed a prostate-specific lentiviral vector based on the promoter of the prostate-specific antigen (PSA). The PSA promoter-based lentiviral vector has been used to deliver the diphtheria toxin A (DTA) gene into prostate cancer cells, and has shown promising tissue-specific eradication of prostate cancer cells in cell culture. To evaluate the efficacy of eradicating human prostate cancer cells in vivo, we used human LNCaP prostate xenografts in nude mice as an animal model and found that with a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…[5][6][7][8]10 Apart from diphteria toxin and Pseudomonas exotoxin, other toxins such as streptolysin O and CPE came into focus. The two latter toxins are both pore-forming proteins, of which streptolysin O is rather unspecific, whereas CPE possesses specificity in action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8]10 Apart from diphteria toxin and Pseudomonas exotoxin, other toxins such as streptolysin O and CPE came into focus. The two latter toxins are both pore-forming proteins, of which streptolysin O is rather unspecific, whereas CPE possesses specificity in action.…”
Section: Discussionmentioning
confidence: 99%
“…4 Particularly for the treatment of refractory tumors, use of these toxins represents an applicable option and was tested in vitro and in vivo to treat various cancers, and have also been efficiently used in gene therapeutic applications. [5][6][7][8] The most extensively used toxins are diphteria toxin (Corynebacterium diphteriae) and Pseudomonas exotoxin A (Pseudomonas aeruginosa), which both inhibit protein synthesis by specific ribosylation of elongation factor-2. 4,9 The two toxins were used for the treatment of prostate, pancreatic, ovarian, lung carcinoma and glioblastoma with promising therapeutic efficacies, and exerted also therapeutic efficacy in gene therapy approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A patient-derived PSA promoter inserted into an HIV-1-based vector has driven efficient transgenic activity in prostate cells with satisfactory efficacy and specificity in in vitro as well as in vivo experiments [132]. More recently, a PSA promoter-based HIV-1 vector has been used to deliver the diphtheria toxin A gene into prostate cancer cells, and has shown promising tissuespecific eradication of prostate cancer cells in cell culture and in a mouse tumor model [133].…”
Section: Transcriptional Targetingmentioning
confidence: 99%
“…12 Recent studies have begun to examine their utility in cancer gene therapy. Pellinen et al 14 reported a 50-95% lentiviral gene transfer efficiency in studies of 42 tumor cell lines from 10 different human tumor types, and lentiviralmediated inhibition of cell growth and/or tumor formation in athymic mice have been demonstrated in prostate cancer, [15][16][17][18] liver cancer, 19 oral squamous cancer, 20 cervical cancer 21 and melanoma. 19,22 We chose to evaluate the effect of lentiviral vector-mediated NEP transfer in NEP-deficient DU145 cells.…”
Section: Introductionmentioning
confidence: 99%